Optimization of α-Amylase Extraction Parameters of Rice Bran Oil (RBO) by Response Surface Methodology - Astrilia Damayanti; Bayu Triwibowo; Megawati; Ima Winaningsih; Ahmed Tessario Ekanuramanta; Rummana Khoirootin Khisan (ASEAN Journal of Chemical Engineering, 2024)
Rice bran oil (RBO) is known as a vegetable oil that has various health benefits; it is extracted from the outer layer (bran) of rice grains using an enzymatic extraction process (Aqueous Enzymatic Extraction, AEE) in the form of α-amylase. The research goals of this study are to determine the optimal processing condition for RBO extraction with α-amylase. The processing parameters were optimized using Response Surface Methodology (RSM) in conjunction with Central Composite Design (CCD). RBO extraction with α-amylase parameters such as the incubation temperature (A) 35, 50, and 65 oC and incubation time (B) 2, 3, and 4 hours to optimize the processing condition. RBO yield (%) and free fatty acid (FFA) were analyzed. A statistical model predicted that the highest conversion yield of RBO would be 1.533% at the following optimized reaction conditions: reaction temperature of 50 oC and time of 4.41 h. Experiments performed at the predicted optimum conditions yielded 1.663% better than the predicted value. A quadratic model was selected to estimate the RBO extraction with α-amylase based on the analysis of variance (ANOVA) of the findings from several models. The linear regression coefficient (R2) between experiments and different response values in the model was 0.97 for RBO yield and 0.8929 for FFA of RBO. The optimal conditions based on all process variables (incubation temperature of 51 oC and incubation time of 4 h) were determined by Derringer’s desired function methodology. Under the conditions mentioned, the yield and FFA of RBO were 1.6% and 7.3%, respectively. All the optimizing parameters and results were validated by regression analysis model fit data using p-value (<0.05), R2 value (yield and FFA of RBO were 0.9749 and 0.8929), and desirability value (>0.05).